Strategies and methods for studying the rhizosphere--the plant science toolbox - Neumann, Günter; George, Timothy S; Plassard, Claude (Plant and soil, 2009)
This review summarizes and discusses methodological approaches for studies on the impact of plant roots on the surrounding rhizosphere and for elucidation of the related mechanisms, covering a range from simple model experiments up to the field scale. A section on rhizosphere sampling describes tools and culture systems employed for analysis of root growth, root morphology, vitality testing and for monitoring of root activity with respect to nutrient uptake, water, ion and carbon flows in the rhizosphere. The second section on rhizosphere probing covers techniques to detect physicochemical changes in the rhizosphere as a consequence of root activity. This comprises compartment systems to obtain rhizosphere samples, visualisation techniques, reporter gene approaches and remote sensing technologies for monitoring the conditions in the rhizosphere. Approaches for the experimental manipulation of the rhizosphere by use of molecular and genetic methods as tools to study rhizosphere processes are discussed in a third section. Finally it is concluded that in spite of a wide array of methodological approaches developed in the recent past for studying processes and interactions in the rhizosphere mainly under simplified conditions in model experiments, there is still an obvious lack of methods to test the relevance of these findings under real field conditions or even on the scale of ecosystems. This also limits reliable data input and validation in current rhizosphere modelling approaches. Possible interactions between different environmental factors or plant-microbial interactions (e.g. mycorrhizae) are frequently not considered in model experiments. Moreover, most of the available knowledge arises from investigations with a very limited number of plant species, mainly crops and studies considering also intraspecific genotypic differences or the variability within wild plant species are just emerging.